Blood pressure is associated with tau pathology independent of beta‐amyloid: Developing topics. (7th December 2020) - Rizvi, Batool; Lao, Patrick J; Brickman, Adam M
Abstract: Background: High blood pressure is a risk factor of Alzheimer's disease (AD) but it is unclear whether it plays a direct role in disease pathogenesis. Recent animal work indicates that induced ischemic disease promotes tau hyperphosphorylation, suggesting that vascular risk factors may directly contribute to AD via neurofibrillary tangle pathology. We examined the relationship between blood pressure indicators and tau pathology, measured with Flortaucipir PET, in early Braak regions among older adults with mild cognitive impairment (MCI) or no cognitive impairment (NC) in the Alzheimer's Disease Neuroimaging Initiative (ADNI). Method: A total of 141 ADNI 2 participants (75.6 + 6.72 years old, 53.2% women, 92% White, 33.3% MCI) who underwent Florbetapir (AV‐45) amyloid and Flortaucipir (AV‐1451) tau PET imaging were included in the analyses. Diastolic (DBP) and systolic blood (SBP) pressure measurements from screening visits were considered. We derived mean arterial pressure (MAP; SBP+2(DBP)), pulse pressure (SBP–DBP), and characterized participants as Stage 2 hypertensive (systolic BP > 140 and/or diastolic BP > 90). We examined the association of each blood pressure indicator with tau standardized uptake value ratios (SUVR) in the entorhinal cortex (EC), adjusting for age, sex/gender, MCI diagnosis, time interval between the screening visit and PET visit (4.5 + 1.17 SD years prior to the PET scan), and a cortical amyloid summary measure. We tested interactions between MCI diagnosis and blood pressure. Result: Independent of amyloid pathology, higher systolic pressure (β=0.217, p=0.009), higher MAP (β=0.186, p=0.021), and hypertension (β=0.165, p=0.044) were associated with increased tau deposition in the entorhinal cortex. Of the covariates, amyloid SUVR (βs=0.301‐0.303, p<0.001), and MCI diagnosis (βs=0.165‐0.189, p=0.031–0.049) were also associated with entorhinal cortex tau. The association between MAP and entorhinal cortex tau was stronger in MCI relative to controls (MCI: β=0.330, p=0.037, NC: β=0.086, p=0.321). Conclusion: High blood pressure is associated with future neurofibrillary tangle pathology in early Braak regions, independently of amyloid. Our results are consistent with reports of earlier life hypertension as risk for later life AD. Together with results from recent animal studies, they highlight a potential pathway in which vascular factors promote AD pathogenesis via tau.